A New SLC10A7 Homozygous Missense Mutation Responsible for a Milder Phenotype of Skeletal Dysplasia With Amelogenesis Imperfecta - Laugel-Haushalter, Virginie; Bär, Séverine; Schaefer, Elise; Stoetzel, Corinne; Geoffroy, Véronique; Alembik, Yves; Kharouf, Naji; Huckert, Mathilde; Hamm, Pauline; Hemmerlé, Joseph; Manière, Marie-Cécile; Friant, Sylvie; et al. (Frontiers in Genetics, 2019)
Amelogenesis imperfecta (AI) is a heterogeneous group of rare inherited diseases presenting with enamel defects. More than 30 genes have been reported to be involved in syndromic or non-syndromic AI and new genes are continuously discovered (Smith et al., 2017). Whole-exome sequencing was performed in a consanguineous family. The affected daughter presented with intra-uterine and postnatal growth retardation, skeletal dysplasia, macrocephaly, blue sclerae, and hypoplastic AI. We identified a homozygous missense mutation in exon 11 of SLC10A7 (NM_001300842.2:c.908C>T; p.Pro303Leu) segregating with the disease phenotype. We found that Slc10a7 transcripts were expressed in the epithelium of the developing mouse tooth, bones undergoing ossification, and in vertebrae. Our results revealed that SLC10A7 is overexpressed in patient fibroblasts. Patient cells display altered intracellular calcium localization suggesting that SLC10A7 regulates calcium trafficking. Mutations in this gene were previously reported to cause a similar syndromic phenotype, but with more severe skeletal defects (Ashikov et al., 2018; Dubail et al., 2018). Indeed, the study by (Dubail et al., 2018) described two patients with a homozygous splice mutations in intron 9 c.774-G>A, c.773+1G>A, two with a homozygous missense mutations c.221T>C and c.388G>A and two with a stop mutation c.514C>T. Ashikov et al., 2018 reported two siblings patients with a SLC10A7 compound heterozygous mutation p.Gly112Asp and c.722–16A>G. Therefore, phenotypes resulting from a mutation in SLC10A7 can vary in severity. However, AI is the key feature indicative of SLC10A7 mutations in patients with skeletal dysplasia. Identifying this important phenotype will improve clinical diagnosis and patient management.